Nickel induced allergic contact stomatitis in treatment using fixed orthodontic appliance - Elih, E. (Universitas Padjadjaran, 2007)
Hypersensitivity towards the metals used in fixed orthodontic is sometimes seen in patients who receive orthodontic treatment with clinical symptoms found intraorally. Nickel is the metal that may cause sensitivity and often causes slow hypersensitivity reaction (immune response type IV) because nickel is the main component of orthodontic alloy. The allergic reaction is found in the form of oral inflammation triggered by the corrosion of orthodontic alloy. The allergic reaction is seen in the form of oral inflammation triggered by corrosion of orthodontic materials and continuous nickel particle release. Young patients, especially female patients, with allergic reaction show a predisposition of NiACS (Nickel Induced Allergic Contact Stomatitis) clinical symptoms. Therefore, dentists and orthodontists should be more careful and cautious in doing a clinical examination to patients through data collecting data on history of abnormalities and health history in the effort of making diagnosis and plan appropriate treatment.